Image of "Xinjiang Vocational Education and Training Centers": content analysis of news report on Chinese mass media from 2018 to 2020 - Zhang, ShuHan (2021)
Since 9/11 and following terrorist attacks carried out by extremist groups, Powell (2018) pointed out that media coverage of terrorism in the US added the fear of Muslims. Islam also has a long history in China, and Muslims have already been a member of ethnic groups in Chinese. However, China also starts to fight against extremist groups, especially in Xinjiang Uyghur autonomous region due to its geographical and religious specialty. Chinese researchers have noticed the impact of media coverage of Chinese Muslims on public voice and conducted several studies, but there are few studies about the "Xinjiang Vocational Education and Training Centers". Therefore, I conducted a content analysis of 159 news reports about "Xinjiang Vocational Education and Training Centers" from 2018 to 2020 to find out how "Xinjiang Vocational Education and Training Centers" are portrayed in Chinese media and what kind of issues are emphasized in news reporting. This article mainly consists of six parts, which are introduction, minority ethnicities and Muslims in China, mass media in China, agenda-setting theory, methodology, and discussion and conclusion. This study found out that news reporting about the "Xinjiang Vocational Education and Training Centers" were quite passive that most of them were responses to international opinions. In addition, these news reports also focused on the human rights issue of the "Xinjiang Vocational Education and Training Centers" that emphasized the establishment of the center was legal and received a good reputation from people at the center.